The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1152/ajpgi.1993.265.4.g699
|View full text |Cite
|
Sign up to set email alerts
|

Origin of D-alanine present in urine of mutant mice lacking D-amino-acid oxidase activity

Abstract: Urine of mutant ddY/DAO- mice lacking D-amino-acid oxidase contained 13 times more D-alanine than that of normal ddY/DAO+ mice. Because D-alanine is a component of bacterial cell walls, the possibility that the urinary D-alanine came from intestinal bacteria was examined. In ddY/DAO- mice that were made germ free at birth and reared in a germ-free environment, the quantity of urinary D-alanine was found to be at a low level comparable to that of the normal mice. When these germ-free mice were made gnotobiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…The present investigation showed that CTN inhibited DAO using D-Ala, which may be constantly metabolized by DAO [24], as the substrate, and the inhibition was confirmed by two methods. Although CTN is regarded as an effective indicator of uremia, its toxicity has not been substantiated.…”
Section: Discussionsupporting
confidence: 60%
“…The present investigation showed that CTN inhibited DAO using D-Ala, which may be constantly metabolized by DAO [24], as the substrate, and the inhibition was confirmed by two methods. Although CTN is regarded as an effective indicator of uremia, its toxicity has not been substantiated.…”
Section: Discussionsupporting
confidence: 60%
“…Although these 2 enantiomers appear to be identical, chiral molecules are fundamentally different. The glutamic acid found in protein is L-glutamic acid only, whereas D-glutamic acid is not found naturally in higher organisms but only in the cell walls of certain bacteria (59)(60)(61). Manufactured or processed free glutamic acid always contains some D-glutamic acid (59,62,63), which is unavailable for peptide and protein synthesis and may even inhibit enzymes.…”
Section: Natural Compared With Processed Free Glutamic Acidmentioning
confidence: 99%
“…Because no DAO activity is detected in the frontal brain areas (for example, the cerebrum and hippocampus) of both strains, the difference between the D-Ala amounts in the two strains was not caused by the DAO activities in the corresponding brain areas. Konno et al reported that a large part of D-Ala in the urine of ddY/DAO Ϫ mice was derived from the cell wall of intestinal bacteria, 67) and Nagata et al demonstrated that the amounts of D-Ala in the brains of ddY/DAO Ϫ mice significantly increased after the oral administration of D-Ala. 65) These reports indicate that the amount of D-Ala in the mammalian brain was affected by the D-Ala amount of exogenous origin. In our research, 22) the serum levels of D-Ala were 8.8Ϯ1.4 nmol/ml in the ddY/DAO ϩ mice, and 134.6Ϯ 16.5 nmol/ml in the ddY/DAO Ϫ mice.…”
Section: Distribution Of D-amino Acids In the Brains Of Mutant Mice Lmentioning
confidence: 99%